Properties of mixture of hemp bast and softwood pulp for filter paper manufacture - Piyawan Yimlamai; Korawit Chitbanyong; Kapphapaphim Wanitpinyo; Buapan Puangsin; Kawinthida Nanta; Somwang Khantayanuwong; Sawitree Pisutpiched; Tanapon Chaisan; Binqi Fei; Salim Hiziroglu (Heliyon, 2024)
The objective of this study was to investigate the morphological and chemical properties of hemp bast RPF1 variety fiber to be used as a potential raw material for filter paper production.Experimental handsheet samples with basis weight of 20 g/m2 were manufactured using mixture of hemp and softwood pulp at various beating levels. The average fiber length and width of hemp bast fiber were determined as 5.76 mm and 32.53 μm, respectively. It was also found that the hemp bast fiber had rigid thick cell wall with small size of lumen. The overall chemical properties of hemp bast were similar to those fibers from other bast sources as well as softwood fibers. It seems that hemp bast was easily pulped under various soda process conditions yielding pulp ranging from 51.36 % to 52.56 % and Kappa numbers ranging from 2.89 to 8.18. Based on the findings in this study hemp bast fiber could be considered as a potential to manufacture filter paper with accepted characteristics.